Cost of skeletal-related events in European patients with solid tumours and bone metastases: data from a prospective multinational observational study. (May 2013) - Hechmati, G.; Cure, S.; Gouépo, A.; Hoefeler, H.; Lorusso, V.; Lüftner, D.; Duran, I.; Garzon-Rodriguez, C.; Ashcroft, J.; Wei, R.; Ghelani, P.; Bahl, A.
Abstract Objectives: Patients with bone metastases often experience skeletal-related events (SREs: radiation or surgery to bone, pathologic fracture, and spinal cord compression). This study examined health resource utilization and costs associated with SREs. Methods: Data presented are from the European cohort (Germany, Italy, Spain, and the UK) of patients with solid tumours enrolled in a multi-national, prospective, observational study in patients with solid tumours or multiple myeloma. Patients with Eastern Cooperative Oncology Group score 0–2 and life expectancy ≥6 months, who experienced an SRE up to 97 days before enrolment, were eligible. Health resource utilization associated with SREs (including number/length of inpatient stays, numbers of procedures and outpatient visits) were collected through chart review for up to 97 days before enrolment and prospectively during follow-up. Country-specific cost calculations were performed. Results: In total, 478 eligible patients contributed 893 SREs to this analysis. Radiation to bone occurred most frequently (66% of total). Spinal cord compression (7%) and surgery to bone (10%) were the least common events, but most likely to require inpatient stays. The most costly SREs were also spinal cord compression (mean per SRE across countries, €4884–€12, 082) and surgery to bone (€3348–€9407). Inpatient stays were the main cost drivers. Limitations: Health resource utilization used to calculate the costs associated with SREs may have been under-estimated as a result of exclusion of patients with low performance status or life expectancy; unavailable information and exclusion of resource consumption associated with pain. Thus, the estimate of associated costs is likely to be conservative. Conclusions: SREs result in considerable health resource utilization, imposing a substantial financial burden driven by inpatient stays. Treatments that prevent/delay SREs may help ease this burden, thereby providing cost savings across European healthcare systems.